Early Childhood Anti-Violence Education in The Perspective of Psychology - Syarbaini, Eni Rosda (Indonesian Journal of Islamic Early Childhood Education, 2016)
Early age children is nation next generation. Government gives serious attention toward early childhood education which is pointed out by PP No. 60 th. 2013 about the integrative and holistic service of early childhood development. Children violence might be occurred everywhere, it could be in the family, on the street and children trafficking. Children violence is a social problem that has a big impact toward psychological, physical, mental, and the growth of children. To prevent this violence, government, society, teachers and parents must involve intensively. Government has issued the law no. 35 th. 2014 about children care. Early childhood must be protected from any kinds of violence. Education for early childhood must be done using learning approach through play games, interactive, children centered, and in joyful atmosphere. Keywords: fun education for early childhood, anti violence, psychology. Anak usia dini adalah generasi penerus bangsa. Pemerintah memberikan perhatian yang serius terhadap pendidikan anak usia dini yang ditunjukkan dengan Peraturan Presiden Nomor 60 tahun 2013 tentang Pelayanan Pengembangan Anak Usia Dini Holistik Integratif. Kekerasan terhadap Anak dapat terjadi dimana-mana, seperti dalam lingkungan keluarga, di jalanan, dan perdaganagan anak. Kekerasan terhadap anak merupakan masalah sosial memiliki dampak besar terhadap psikologis, fisik, mental, dan tumbuh kembang anak. Untuk pencegahan kekerasan terhadap anak, dituntut peran aktif orang tua, pendidik, masyarakat, dan Pemerintah. Pemerintah menerbitkan Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak. Anak usia dini harus dilindungi dari segala bentuk kekerasan. Pendidikan Anak Usia Dini dilakukan dengan pendekatan belajar melalui bermain, interaktif, berpusat pada anak, dan dalam suasana yang menyenangkan. Kata Kunci: PAUD Menyenangkan, Anti Kekerasan, Psikologi.